Macroeconomic Forces and Stock Returns in Vietnam - Phan, Van Hang (2008)
Capital market development, especially the appearance of Vietnamese equity market recently has a strategic importance in the economic growth and structural reform process of Vietnam (Chun et al, 2003). This dissertation focuses on the impacts of macroeconomic forces on stock market returns in Vietnamese stock market which has not been investigated in detail before, and thereby to contribute further literature on this new emerging stock market. Specifically, the research will intensively investigate the influence of fundamental economic variables on stock returns from three main aspects of the economy consisting of domestic financial sector, real economic activities and international factors by using some theoretical explanations and employing some econometric models. The data used in this study are quarterly stock prices indexes of Ho Chi Minh Securities Trading Center (HOSTC) and a set of macroeconomic variables since the establishment of Vietnamese stock market in 2000 until the second quarter of 2008. This paper, thus, represents one of the first comprehensive studies concerning about the effect of macroeconomic factors on Vietnamese stock market returns. In general, it is found strong evidences that all of the global and domestic macroeconomic factors including inflation rates, industrial production output, foreign exchange rates and world oil prices impact stock price returns in this equity market. The result for interest rates variable does not show direct relationship between interest rates and stock returns, however, it affects on stock market as an indirect contributory factor. Besides the observation of short run relationships between them, the VECM test also indicates significant long term relationships in stock market return which will in the long term converge toward to its long run equilibrium. The results of this study hence are indeed useful for individual and institution investors, managers, and more importantly is for policy maker.